A toolkit for costing environmental health services in healthcare facilities - Darcy M. Anderson (IWA Publishing, 2021)
Environmental health services (EHS) are critical for safe and functional healthcare facilities (HCFs). Understanding costs is important for improving and sustaining access to EHS in HCFs, yet the understanding of costs is poor and no tools exist to specifically support costing EHS in HCFs in low- and middle-income countries. We developed a toolkit to guide the following steps of costing EHS in HCFs: defining costing goals, developing and executing a data collection plan, calculating costs, and disseminating findings. The costing toolkit is divided into eight step-by-step modules with instructions, fillable worksheets, and guidance for effective data collection. It is designed for use by diverse stakeholders involved in funding, implementation, and management of EHS in HCFs and can be used by stakeholders with no prior costing experience. This paper describes the development, structure, and functionality of the toolkit; provides guidance for its application; and identifies good practices for costing, including pilot testing data collection tools and iterating the data collection process, involving diverse stakeholders, considering long-term costs, and disaggregating environmental costs in records to facilitate future costing. The toolkit itself is provided in the Supplementary Material. Highlights We developed a toolkit to cost environmental health services in healthcare facilities, comprising eight modules and worksheets.; Costing-stakeholders should test tools, iterate data collection steps, involve diverse stakeholders, and consider life cycle costs.; Costing-stakeholders should test tools, iterate data collection steps, involve diverse stakeholders, and consider long-term costs.; Information management systems should code and disaggregate environmental costs to facilitate future costing.;